SEC-Translocon Dependent Extracytoplasmic Proteins of Candidatus Liberibacter asiaticus - Prasad, Samiksha; Xu, Jin; Zhang, Yunzeng; Wang, Nian (Frontiers in Microbiology, 2016)
Citrus Huanglongbing (HLB) is the most destructive citrus disease worldwide. HLB is associated with three species of the phloem-limited, gram-negative, fastidious α-proteobacteria: Candidatus Liberibacter asiaticus (Las), Ca. L. americanus (Lam), and Ca. L. africanus (Laf) with Las being the most widespread species. Las has not been cultured in artificial media, which has greatly hampered our efforts to understand its virulence mechanisms. Las contains a complete Sec-translocon, which has been suggested to transport Las proteins including virulence factors into the extracytoplasmic milieu. In this study, we characterized the Sec-translocon dependent, signal peptide containing extracytoplasmic proteins of Las. A total of 166 proteins of Las_psy62 strain were predicted to contain signal peptides targeting them out of the cell cytoplasm via the Sec-translocon using LipoP, SigalP 3.0, SignalP 4.1, and Phobius. We also predicated SP containing extracytoplasmic proteins for Las_gxpsy and Las Ishi-1, Lam, Laf, Ca. L. solanacearum (Lso), and L. crescens (Lcr). For experimental validation of the predicted extracytoplasmic proteins, Escherichia coli based alkaline phosphatase (PhoA) gene fusion assays were conducted. A total of 86 out of the 166 predicted Las proteins were experimentally validated to contain signal peptides. Additionally, Las_psy62 lepB (CLIBASIA_04190), the gene encodes signal peptidase I, was able to partially complement the amber mutant of lepB of E. coli. This work will contribute to the identification of Sec-translocon dependent effector proteins of Las, which might be involved in virulence of Las.